2012
DOI: 10.3329/birdem.v2i2.12308
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Glycemic Status (HbA1c) at Delivery and Risk of Hypoglycemia in Infants of Diabetic Mothers

Abstract: Objective: To examine the influence of maternal HbA1c level at delivery and risk of hypoglycemia in infants of diabetic mothers. Method: This case-control study was done with sixty neonates born to diabetic mothers in BIRDEM hospital. Out of sixty neonates, 30 neonates who developed hypoglycemia during the first 24 hours of age were considered as cases and another 30 neonates who did not develop hypoglycemia during the first 24 hours were considered as controls. Maternal glycemic status was examined by measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…None of the babies developed hypoglycemia after 3 hours of age. Begum et al 17 found in their study that 50% of infants of diabetic mothers were hypoglycemic at 4 hours of age, whereas Dhananjaya et al 18 found that hypoglycemia was present in 40% of infants of diabetic mothers during first three days of life. Both studies are nearly similar to our study.…”
Section: Discussionmentioning
confidence: 92%
“…None of the babies developed hypoglycemia after 3 hours of age. Begum et al 17 found in their study that 50% of infants of diabetic mothers were hypoglycemic at 4 hours of age, whereas Dhananjaya et al 18 found that hypoglycemia was present in 40% of infants of diabetic mothers during first three days of life. Both studies are nearly similar to our study.…”
Section: Discussionmentioning
confidence: 92%